(untitled) (Research, Society and Development, 2022)
The objective was to report the experience entitled "Medita Rural Series: short breaks in human self-care based on mindfulness", experienced at the Universidade Federal Rural de Pernambuco (UFRPE) during the COVID-19 Pandemic. A dialogic methodology was adopted through the UFRPE channel on the YouTube platform. The synchronous experience of five episodes or mindfulness meditation sessions was cultivated, on Mondays at 9 am, with a maximum duration of thirty minutes per episode. These were intended as brief explanations about posture, theory, mechanisms, and neural networks involved in meditation, and the practice of mindfulness meditation. The videos were recorded and made available on YouTube as a tool to be used asynchronously by technical-administrative education workers, teachers, and the external public at the most favorable time for mindfulness-based self-care breaks. The collection of quantitative data from the episodes of the series “Medita Rural” was carried out through “YouTube Analytics” and the qualitative data were taken from institutional speeches, chat messages, and comments posted on the videos. The results obtained reinforce the importance of mindfulness practice in promoting the well-being of the university community and, especially, in the development of attentional, attitudinal, and emotional regulation skills and cognitive flexibility during the COVID-19 Pandemic. The provisionally of the results of the “Medita Rural” series signaled some limitations of the experience, leaving open other possibilities for the delivery of virtual mindfulness in educational environments.